MKP-3 Has Essential Roles as a Negative Regulator of the Ras/Mitogen-Activated Protein Kinase Pathway during Drosophila Development - Kim, Myungjin (American Society for Microbiology, 2004)
Mitogen-activated protein kinase (MAPK) phosphatase 3 (MKP-3) is a well-known negative regulator in the Ras/extracellular signal-regulated kinase (ERK)-MAPK signaling pathway responsible for cell fate determination and proliferation during development. However, the physiological roles of MKP-3 and the mechanism by which MKP-3 regulates Ras/Drosophila ERK (DERK) signaling in vivo have not been determined. Here, we demonstrated that Drosophila MKP-3 (DMKP-3) is critically involved in cell differentiation, proliferation, and gene expression by suppressing the Ras/DERK pathway, specifically binding to DERK via the N-terminal ERK-binding domain of DMKP-3. Overexpression of DMKP-3 reduced the number of photoreceptor cells and inhibited wing vein differentiation. Conversely, DMKP-3 hypomorphic mutants exhibited extra photoreceptor cells and wing veins, and its null mutants showed striking phenotypes, such as embryonic lethality and severe defects in oogenesis. All of these phenotypes were highly similar to those of the gain-of-function mutants of DERK/rl. The functional interaction between DMKP-3 and the Ras/DERK pathway was further confirmed by genetic interactions between DMKP-3 loss-of-function mutants or overexpressing transgenic flies and various mutants of the Ras/DERK pathway. Collectively, these data provide the direct evidences that DMKP-3 is indispensable to the regulation of DERK signaling activity during Drosophila development.